2002
DOI: 10.18785/goms.2001.06
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habits of Dwarf Goatfish (Upeneus parvus: Mullidae) on the Continental Shelf in the Gulf of Mexico

Abstract: Feeding habits of dwarf goatfish on the continental shelf off Alvarado, Veracruz, Mexico, were analyzed to determine seasonal variation and size-class changes in diet composition and trophic overlap between size classes. Food was found in 63% of the 1,437 dwarf goatfish guts analyzed. The 52 dietary items identified consisted mainly of crustaceans, with Solenocera vioscai being the most important prey. Dwarf goatfish exhibited seasonal and size-class changes in prey consumption. Despite the high number of prey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, Sweatman (1984) found that S. englemani were active hunters, individuals move frequently over distances of up to 1.5 m between elevated rock from which they scan the surroundings for prey. Regardless of which habitat type they forage within, the important prey listed above are also abundant species in the GOM, and are considered key species in the dynamics of this marine community (Yañez‐Arancibia et al., 1985; Robins and Ray, 1986; Yáñez‐Arancibia and Sánchez‐Gil, 1988; Campos‐Dávila et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, Sweatman (1984) found that S. englemani were active hunters, individuals move frequently over distances of up to 1.5 m between elevated rock from which they scan the surroundings for prey. Regardless of which habitat type they forage within, the important prey listed above are also abundant species in the GOM, and are considered key species in the dynamics of this marine community (Yañez‐Arancibia et al., 1985; Robins and Ray, 1986; Yáñez‐Arancibia and Sánchez‐Gil, 1988; Campos‐Dávila et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Johnius borneensis feeds mainly on fishes and crustaceans, which is compliant with the present study (Theisen 2009 ). As bottom dwellers, members of the genus Upeneus mainly feed on benthic invertebrates, fish, and polychaetes (Kaya et al 1999 ; Campos-Dávila et al 2002 ; Prabha and Manjulatha 2008 ). Here, in both U. asymmetricus and U. moluccensis , fish dominated the diet and crustaceans only played a minor role.…”
Section: Discussionmentioning
confidence: 99%